Implantology Aesthetics in Dentistry (International Journal of Food and Nutritional Sciences, 2022)
Background: People have understood the value of physical attractiveness and appearance since ancient times. Greek art meticulously examined the "divine proportion" connected to aesthetics and harmony in the disciplines of architecture, sculpture, music, and the human body and face in order to address the concept of beauty. The golden ratios also assist modern societies in defining ideal beauty. Levin introduced the golden ratios to teeth and the anterior aesthetic region in 1978. Esthetics are portrayed in the media as being connected to wellbeing and social success. In today's world, facial attractiveness is especially significant since it affects social possibilities, professional performance, and employment chances in addition to self-esteem. Restoring function and meeting patients' aesthetic needs are the primary objectives of plastic surgery around teeth and implants. Many research have discussed plastic surgery methods and surgical results (surrogate end points), and dentists have assessed aesthetic outcomes in certain trials. However, relatively few studies have included patient requirements and wishes.